Jae Kyu Park (ed), Korea and Indonesia: Toward Inter-regional Cooperation, Seoul, Institute for Far Eastern Studies, Kyungnam University, 1981, pp. 141. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1984)
-